MINIMAL REGULATION OF PLATELET ACTIVITY BY PECAM-1 - Dhanjal, Tarvinder S. (2007)
OBJECTIVES: PECAM-1 is a member of the superfamily of immunoglobulins (Ig) and is expressed on platelets at moderate level. PECAM-1 has been reported to have contrasting effects on platelet activation by the collagen receptor GPVI and the integrin, α(IIb)β(3), even though both receptors signal through Src-kinase regulation of PLCγ2. The present study compares the role of PECAM-1 on platelet activation by these two receptors and by the lectin receptor, CLEC-2, which also signals via PLCγ2. METHODS & RESULTS: Studies using PECAM-1 knockout-mice and cross-linking of PECAM-1 using specific antibodies demonstrated a minor inhibitory role on platelet responses to the above three receptors and also under some conditions to the G-protein agonist thrombin. The degree of inhibition was considerably less than that produced by PGI(2), which elevates cAMP. There was no significant difference in thrombus formation on collagen in PECAM-1(−/−) platelets relative to litter-matched controls. CONCLUSIONS: The very weak inhibitory effect of PECAM-1 on platelet activation relative to that of PGI(2) indicate that the Ig-receptor is not a major regulator of platelet activation.